DCCA cross-correlation in blue-chips companies: A view of the 2008 financial crisis in the Eurozone - Guedes, Everaldo (2020)
In this paper we analyze the blue-chips (up to 50% of the total index) companies in the Eurozone. Our motivation being analysis of the effect of the 2008 financial crisis. For this purpose, we apply the DCCA cross-correlation coefficient (ρDCCA) between the country stock market index and their respective blue-chips. Then, with the cross-correlation coefficient, we qualify and quantify how each blue-chip is adherent to its country index, evaluating the type of cross-correlation among them. Subsequently, for each blue-chip, we propose to study the 2008 financial crisis by measuring the adherence between post and pre-crisis. From this analysis, we can construct an adhesion map of each company with respect to the global index. Our database is formed of 12 Eurozone countries.